In memoriam: José Luis Villar Palasí, Educate for innovation. (Journal of Parents and Teachers, 2012)
José Luis Villar Palasí, education minister in the 60’s and 70’s decades, one of the forefathers of the reforms of the Education Law or Moyano Law, established the bases of the modern educative system, started the distance education, bilingual teaching in the bilingual regions of Spain and the system of scholarships.
Keywords: in memoriam